Therapeutic levetiracetam monitoring during pregnancy: "mind the gap". (May 2019) - Berlin, Maya; Barchel, Dana; Gandelman-Marton, Revital; Brandriss, Nurit; Blatt, Ilan; Ziv-Baran, Tomer; Neufeld, Miri Y.; Dinavitser, Natalie; Kohn, Elkana; Shaniv, Dotan; De-Haan, Tal; Ofek, Fanny; et al.
Background: Epilepsy is one of the most common chronic neurological conditions and its treatment during pregnancy is challenging. Levetiracetam (LEV) is an antiepileptic medication frequently used during pregnancy. Only a few small studies have been published on LEV monitoring during pregnancy, demonstrating decreased serum LEV levels during the first and second trimester; however, the most significant decrease was observed during the third trimester of pregnancy. In this study we aimed to evaluate LEV pharmacokinetics during different stages of pregnancy. Methods: We followed up and monitored serum levels of pregnant women treated with LEV for epilepsy. Results: Fifty-nine women with 66 pregnancies during the study period were included. The lowest raw LEV serum concentrations were observed during the first trimester. Compared with the pre-pregnancy period, raw serum concentration was lower by 5.76 mg/L [95% confidence interval (CI) (2.78, 8.75), p  = 0.039] during the first trimester. Comparing the decrease in the first trimester with either the second or the third, no significant changes were observed ( p  = 0.945, p  = 0.866). Compared with pre-pregnancy measurements, apparent clearance was increased by 71.08 L/day [95%CI (16.34, 125.83), p  = 0.011] during the first trimester. About 30% of LEV serum levels during pregnancy were below the laboratory quoted reference range. Conclusions: Raw LEV serum levels tend to decrease during pregnancy, mainly during the first trimester contrary to previous reports. Monitoring of LEV serum levels is essential upon planning pregnancy and thereafter if pre-pregnancy LEV levels are to be maintained. However, more studies are needed to assess the correlation with clinical outcome.